Turbin Hibrid Bi-Directional Sebagai Pemanen Energi pada Thermoacoustic Engine - Winarto, Eko Wismo; Sugiyanto, Sugiyanto; Siswantoro, Soeadgihardo; Djati, Isworo (Jurnal Rekayasa Mesin, 2021)
Bi-directional turbines that are commonly applied to convert wave energy into motion energy are the types of Impulse turbines and Wells turbines. Both types of turbines each have advantages and disadvantages. In this research, hybrid turbine type is designed and made to bridge the weaknesses in impulse turbine and turbine wells. Hybrid turbines are made by placing impulse turbines on the outside while turbine wells placed on the inside. In this research, the variation of hybrid bi-directional turbine design aims to find out the most optimal design of this turbine type. Six variations were carried out including a hub to tip ratio of 0.5 with 4 and 5 Wells blades, a hub to tip ratio of 0.6 with 4 and 5 Wells blades, and a hub to tip ratio of 0.7 with 4 and 5 Wells blades. From the test results on thermoacoustic engine media, based on the hub to tip ratio, the most optimal hub to tip ratio is in the order of 0.7 then 0.6, and 0.5. Whereas based on the number of Wells blade, obtained the number of Wells blade 5 is more optimal than the number of Wells blade 4.